BIOGAS PRODUCTION FROM RUMINAL BIOMASS OF DIFFERENT GENETIC GROUPS OF SHEEP - dos Santos Araújo, Jocélio; Fernandes, Francivana Pedrosa; dos Santos Cabral, Ismael; de Oliveira Maia Parente, Michelle; Parente, Henrique Nunes; Rodrigues, Rosane Claudia (International Journal of Research -GRANTHAALAYAH, 2019)
The objective was to evaluate the biogas production from ruminal biomass of different genetic groups of sheep. Twelve prototypes of experimental biodigesters were used in batch, which were supplied with ruminal biomass of two genetic groups of sheep (Rabo Largo and Santa Inês) that during a period of confinement were fed with two diets characterized as high and low concentrate, with proportions of 70% and 30%, respectively. After the animals were slaughtered, all ruminal contents were collected according to the genetic groups and feeding levels, being this the materials that constituted ruminal biomass. A completely randomized design with four treatments and three replications was used. The analyzed variables were temperature, pH, biogas production and pressure. The inoculation of the ruminal biomass of the different genetic groups of sheep studied presented favorable conditions to produce biogas, demonstrating efficiency in the anaerobic digestion process.